1972
DOI: 10.2134/agronj1972.00021962006400060011x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Date on Sunflower Yield, Oil, and Plant Characteristics1

Abstract: Planting date studies were conducted on sunflowers (Helianthus annuus L.) from 1969 through 1971 at Experiment, Ga. to evaluate the optimum time of planting on seed yield, oil percentage, oil composition, and other plant characteristics. Seeds of ‘Peredovik’ and ‘Krasnodarets’ varieties were planted at each date ranging from March 11 to July, 22. Highest seed yields and oil percentage of seeds were produced when sunflowers were planted from mid‐March through April. Fatty acid composition of seed oil varied con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…A decrease in oil concentration in late-planted sunflower was reported by UNGER (1980) in an earlier study. In contrast, ANDERSON et al (1978) and JOHNSON and JELLUM (1972) observed that oil concentration was not affected by planting date.…”
Section: Sources Of Variationmentioning
confidence: 85%
See 1 more Smart Citation
“…A decrease in oil concentration in late-planted sunflower was reported by UNGER (1980) in an earlier study. In contrast, ANDERSON et al (1978) and JOHNSON and JELLUM (1972) observed that oil concentration was not affected by planting date.…”
Section: Sources Of Variationmentioning
confidence: 85%
“…In North Dakota under dryland conditions, ALESSI et al (1977) recommended planting sunflower before mid-June for high seed yield and oil concentration. JOHNSON and JELLUM (1972) found that seed yield and oil concentration were highest when sunflower was planted between mid-March and April.…”
Section: Introductionmentioning
confidence: 99%
“…Downes (1974) and Harris et al (1978) showed that oil percent decreased as temperature increased. In contrast, Johnson and Jellum (1972) and Unger (1980) found that the oil percent of seed from late-planted sunflower maturing during cooler weather was lower than from earlier-planted sunflower maturing during warmer weather. These different responses may have been due to temperature effects at specific developmental stages or to factors other than temperature.…”
mentioning
confidence: 83%
“…In short, different sowing times might expose the crop to different environmental conditions during grain filling and oil synthesis, resulting in a possible alteration in yield and quality attributes (Connor and Sadras 1992). Several studies have demonstrated changes in sunflower oil concentrations with different sowing times (Johnson and Jellum 1972;Unger 1980;Beard and Geng 1982;Andrade 1995;Bange et al 1997).…”
mentioning
confidence: 99%